Ex-Post impact assessment review of IFPRI’s research program on social protection, 2000–2012 - Nelson, Suzanne; Brown, Vicky; Presnall, Carrie; Downen, Jeanne; Frankenberger, Timothy R. (International Food Policy Research Institute, 2015)
This report assesses the impact of IFPRI’s social-protection research program (GRP28) from 2000 to 2012 (including its predecessor, MP18). The assessment includes an extensive review of public goods produced by the program, stakeholder perceptions of the program’s public goods and research activities, case studies (Bangladesh, London, Mexico, Rome, and Washington, DC), and policy or programming changes that resulted from IFPRI-sponsored research, capacity strengthening, and research-policy linkages between 2000 and 2012. Over 40 interviews were conducted with national stakeholders, donors, IFPRI staff, government officials, and individuals who participated in or had knowledge of IFPRI’s activities regarding social protection during this timeframe. IFPRI’s social-protection research activities conducted under the GRP28 are ongoing and extend beyond the 2012 endline of this assessment. GRP28 research activities initiated during the latter part of the 12-year timeframe (that is, in 2010, 2011, or 2012) are limited or absent from this assessment if results had not been published at the time the study was initiated early in the summer of 2014.